The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1975
DOI: 10.2307/1589191
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Some Physical Factors on Survival of Marek's Disease Vaccine Virus

Abstract: Cell-associated Marek's disease (MD) vaccine was suspended at dilutions normally used for vaccination in seven commercially available diluents and in tryptose phosphate broth. The stability of diluted vaccines was determined by assay in cell cultures subjected to 0 to 37 C for 0 to 90 minutes. Optimum holding temperatures for MD vaccine virus survival varied with the specific diluents employed. Some diluents afforded greatest survival when dilution was at 0 C and held at 0 C, while others performed best when d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Osmotic pressure in the diluent was manipulated from 0 to 1000 mOsm/kg by addition of 0 to 3.18% sodium chloride respectively. There was a correlation between increased osmotic pressure and decreased virus survival [229]. Pressures above 475 mOsm/kg severely depressed virus survival, where the normal range of commercial diluents was 288 to 372 mOsm/kg [229].…”
Section: Vaccination Failures and Factors Influencing MD Outbreaksmentioning
confidence: 97%
See 1 more Smart Citation
“…Osmotic pressure in the diluent was manipulated from 0 to 1000 mOsm/kg by addition of 0 to 3.18% sodium chloride respectively. There was a correlation between increased osmotic pressure and decreased virus survival [229]. Pressures above 475 mOsm/kg severely depressed virus survival, where the normal range of commercial diluents was 288 to 372 mOsm/kg [229].…”
Section: Vaccination Failures and Factors Influencing MD Outbreaksmentioning
confidence: 97%
“…Despite limitations such as procedural differences (thawing the vaccine under cold running water rather than with a room temperature water bath) and testing commercial diluents available at the time, the study gives insights into those factors affecting MD vaccines viability. The results showed that temperature plays a role on virus survival and that holding the vaccine diluent at 0 degrees Celsius was optimal regardless of initial diluent temperatures into which the vaccine was reconstituted [229]. The temperature of the diluent to which the vaccine was added also played a role, though some diluents performed best when vaccine was mixed at 25 degrees C and others when mixed at 0 degrees C. In a different study [230], it was found that reconstituting the vaccine in a refrigerated diluent (4 degrees C) rather than a room temperature diluent could lower the titers by 20%.…”
Section: Vaccination Failures and Factors Influencing MD Outbreaksmentioning
confidence: 99%
“…Therefore, MD vaccines are administered to chicks at hatch by subcutaneous or intramuscular inoculation or in ovo at ED18 via amniotic or intraembryonic route (Sharma and Burmester, 1982). Other factors such as mixing with antibiotics (Colwell et al, 1975;Eidson et al, 1978), joint administration with other vaccines (Rosenberger, 1983), or long delays in vaccination after reconstitution can also decrease vaccine titers. Only viable infected cells are capable of transmitting the vaccine virus, so handling is of crucial importance for a vaccine to retain its efficacy (Halvorson and Mitchell, 1979).…”
Section: • Vaccine Administrationmentioning
confidence: 99%
“…For example, vaccine particles grown in culture at specific ionic strengths may reequilibrate when introduced into solutions of different ionic strength resulting in osmotic swelling or contraction that diminishes the integrity of the vaccine. Marek's disease vaccine has been shown to be extremely sensitive to osmotic changes with an osmolarity of 745 mOsm/kg markedly reducing vaccine virus survival 24…”
Section: Liquid Formulationsmentioning
confidence: 99%